Commentary on "O3 variability in the troposphere as observed by IASI over 2008–2016: Contribution of atmospheric chemistry and dynamics" by Wespes et al. Issue 11 (1st June 2017) - Payne, Vivienne H.; Neu, Jessica L.; Worden, Helen M.
Abstract: Evaluation and attribution of variability and trends in tropospheric ozone requires consideration not only of the spatial distribution of ozone precursor emissions and their changes in time but also of variations in transport at regional and global scales. Satellite measurements of tropospheric ozone are now beginning to provide the vertical resolution, length of record, and density of coverage needed for disentangling the factors that influence variability and trends. A recent study by Wespes et al. (2017, https://doi.org/10.1002/2016JD025875), utilizing an 8 year data set from the Infrared Atmospheric Sounding Instrument (IASI) satellite instrument to perform a global scale, spatially resolved analysis of influences of geophysical drivers on tropospheric ozone variability, represents a key step toward understanding long‐term changes in the distribution of tropospheric ozone and its corresponding impacts on air quality, chemistry, and climate. Key Points: Commentary on Wespes et al. (2017) manuscript on O3 variability in the troposphere Satellite measurements provide long‐term, densely sampled, and vertically resolved tropospheric O3 record Wespes et al. study represents key step toward understanding long‐term changes in tropospheric O3